Multidisciplinary evaluation in cognitive behavioral sleep medicine: Leveraging behavioral neurology and sleep medicine expertise: Developing topics. (7th December 2020) - Karageorgiou, Elissaios; Sykara, Konstantina; Ramirez, Jeronimo Martin; Andronas, Nikolaos; Mavragani, Evdoxia; Mougias, Michalis; Tsekou, Hara; Karageorgiou, Klimentini E
Abstract: Background: Cognitive Behavioral Sleep Medicine is a rapidly growing discipline that aims at the comprehensive evaluation and treatment of people with cognitive or sleep symptoms, established on the bidirectional relationship between sleep disorders and neurodegeneration. On this basis, we established a comprehensive evaluation protocol for deep phenotyping of cognitive‐sleep syndromes, and present first results on its feasibility and novel cognitive to sleep associations. Method: We enrolled 29 patients (age: 71.5 ± 11.7; education: 9.6 ± 2.8 years) with minor or major neurocognitive disorder due to predicted Alzheimer's disease with various degrees of vascular comorbidity (MMSE = 26.0 ± 4.3) through the Sleep & Memory Center of the Neurological Institute of Athens. All patients underwent comprehensive clinical evaluations, including cognitive (Cognitive Behavioral Symptoms [CBS] score) and sleep questionnaires (Insomnia Severity Index [ISI]; Epworth Sleepiness Scale [ESS]), biochemical, imaging, and within‐day neuropsychological testing, whereas six patients have further completed novel sleep‐mediated neuropsychological tests, actigraphy and polysomnography. Exploratory analyses using Pearson ρ or Kendall τ, accordingly, were performed to examine associations of subjective complaints and daily functioning to objective cognitive and sleep metrics. Result: Non‐memory cognitive CBS scores were highly correlated to sleep CBS scores (ρ, τ ∼ 0.51 ‐ 0.71), as well as ISI (0.56) and ESS (0.54). Memory CBS complaints in contrast correlated more with subjective insomnia symptoms (0.72 to ISI) but not hypersomnia (‐0.15 to ESS). Additionally, the CBS total score was associated to sleep‐mediated 9‐item recall (0.81) and to sleep‐mediated phonemic fluency (‐0.55), an association also noted between ESS to sleep‐mediated 9‐item recall (0.71). Of note, subjective cognitive and sleep complaints were not well correlated to within‐day neuropsychological testing (e.g., 0.13 ‐ 0.36 to MMSE). Patients who underwent actigraphy and polysomnography tolerated all procedures, and those diagnosed with sleep apnea or insomnia are effectively pursuing CPAP treatment and Cognitive Behavioral Therapy for Insomnia respectively. Conclusion: Comprehensive evaluation of sleep and cognitive symptoms is feasible in patients with neurocognitive disorders and allows for deep phenotyping of neurodegenerative diseases. Finally, sleep‐mediated cognitive tests seem to be more sensitive than within‐day tests in reflecting real‐life symptoms, highlighting their potential utility.